A clinical approach to benign breast lesions in female adolescents - Elsedfy, Heba (Acta Biomedica Atenei Parmensis, 2017)
The female breast undergoes two phases of growth and differentiation. The first occurs during fetal life and results in the formation of simple branched ducts, which are able to respond to the hormonal stimuli of maternal origin. The second period of growth occurs at puberty, when the ducts elongate, divide, and form terminal duct lobular units. Breast pathology during adolescence is usually benign and therefore management has to be mostly conservative. Familiarity with the spectrum of breast pathology in this age group is essential. Ultrasound is the imaging modality of choice. Open surgical biopsies can damage the developing breast and therefore availability and expertise with fine needle aspiration biopsy can circumvent this problem.